Production of caprine cloned embryos using somatic cell nuclear transfer / Siti Haslinda Mohd Sharif - Siti Haslinda , Mohd Sharif (2018)
Production of cloned goat embryos using interspecies somatic cell nuclear transfer (SCNT) technique could be applied using cattle oocyte as recipient cytoplast since the source of goat oocytes is limited in our country. The main aim of this study was to produce goat and cattle cloned embryos using intra- and interspecies SCNT technique. Cattle oocytes were retrieved from abattoir-derived ovaries to be used as recipient cytoplasts for subsequent SCNT experiment. Cattle oocytes were then matured in vitro by culturing in in vitro maturation (IVM) medium and denuded in hyaluronidase (0.1%) to remove the cumulus cells on following day. The matured cattle oocytes were selected based on extrusion of first polar body and subjected to enucleation using laser-shooting technique afterwards. Donor karyoplasts derived from goat (Rumpun Asia Sdn Bhd Farm, Selangor) and cattle (Banting abattoir) were harvested and injected into enucleated cattle oocytes. Reconstructed oocytes were then activated and the reconstructed couplets were cultured in vitro in potassium simplex optimisation medium (KSOM) in CO2 incubator (5%, 38.5°C). Cloned embryos development were monitored and recorded for data analysis. All data were presented as mean±SEM and were analysed using one-way ANOVA. The significant differences among treatments were further analysed by Duncan’s Multiple Range Test (DMRT) and P<0.05 was considered significant. In Experiment 1, two IVM durations of cattle oocytes were compared, i.e. Group 1 (22-24 hr) and Group 2 (25-27 hr). The maturation rate of Group 1 (22-24 hr) was significantly higher (P<0.05) than Group 2 (25-27 hr). Group 1 showed significantly higher (P<0.05) compared with Group 2 with the cleavage rates of 69.18% vs. 55.27% (2-cell); 53.09% vs. 38.32% (4-cell); 41.40% vs. 26.92% (8-cell) and 21.26% vs. 9.31% (morula), respectively, except for 2- and 4-cell stages in Group 1. In experiment 2, effect of different types of donor karyoplasts (goat ear fibroblast cells; EFC and goat foetal fibroblast cells; FFC) as well as comparison between fresh and frozen-thawed samples on viability of cells were studied. There were no significant differences in percentages of cells viability between two breeds of ear fibroblast cells (EFC) (Jermasia vs. Boer) in all passages, except for P1 that Boer was significantly higher in percent viability than Jermasia (86.72% vs. 80.44%), respectively. However, there were significant differences of cell viability between fresh and frozen-thawed samples in all passages of EFC and foetal fibroblast cells (FFC). The FFC also showed higher in term of cells viability as oppose to EFC. In experiment 3, intraspecies SCNT was conducted to produce cloned cattle embryos using cumulus cells from cattle as donor karyoplast. The values of cleavage rates in cattle intraspecies SCNT were 53.57% (2-cell), 33.17% (4-cell), 22.15% (8-cell) and 11.90% (morula). There were significant decreases in the cleavage rate at different stages (2-cell until morula) of cloned cattle embryo development (P<0.05). In experiment 4, the efficiency rate of interspecies SCNT of goat-cattle cloned embryos was evaluated using two different sources of donor karyoplast, which were goat EFC and FFC. The results showed that FFC gave significantly higher cleavage rate compared with EFC (P<0.05), 2-cell (64.40% vs. 38.43%), 4-cell (54.24% vs. 24.60%), 8-cell (36.82% vs. 14.54%) and morula (22.10% vs. 7.90%), respectively. In conclusion, cattle and goat cloned embryos could be produced using advanced reproductive techniques such as pathenogenetic activation, intra- and interspecies SCNT techniques. However, using goat FFC was more efficient than EFC as donor karyoplast to produce cloned goat embryos.